Efisiensi dan Kesenjangan Teknologi Usaha Tani Padi Sawah di Pulau Jawa - Mohammad Junaedi; Heny K. S. Daryanto; Bonar M. Sinaga; Sri Hartoyo (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2016)
The characteristics of different provinces led to the use of different technologies among wetland rice farming in Java. Such differences lead to the technologthat resulted in incomparable frontier size among provinces. This study analysed the factors affected on the production, efficiency and how the technological gap in wetland rice farming. Meta-frontier analysis is applied in this article to prove that the measure of the technical efficiency level in four Java Island provinces can not be compared among each other. All variable coefficients production function as expected is positive and significant. This study also shows that the utilization of technical efficiency (TE) were measured based on their respective frontier province could lead to biased and misleading policy decisions, so it needs to be given special notes in its analysis.